Main herbal medicines used in the control of ectoparasites and endoparasites in horses and cattle – Bibliography Review (Research, Society and Development, 2020)
The ecto and endoparasites are responsible for significant losses in Brazilian cattle ranch, and studies related to the control of these diseases are increasing. One way to control these parasitasis is the use of phototherapy. The Brazilian veterinary market consists of various types of products ranging from medicines to animal fodder, dietary supplements and there has recently been room for herbal medicines. The thought that the treatment with plants is simply to make a tea of leaves, causes the use of phytotherapy to be little addressed and explored. In view of the above, the present work aimed to describe the main plants used as herbal medicines in the control of ecto and endoparasitis in horses and cattle. The plants found for the control of ectoparasites were: Cymbopogon nardus L, Aloe vera L, Azadirachta indica, Artemísia vulgaris L, Eucalyptus sp., Chenopodium ambrosioides L. and Syzygium aromaticum. For the control of verminosis were: Allium sativum L, Curcubita pepo L., Momordica charantia, Operculina hamiltonii and Musa sp. With this bibliographic search, it was possible to conclude that the use of phytotherapy in horses and cattle is smaller when compared to use in small ruminants, however, it is a viable alternative to control these diseases.